USE OF THE HEALTH BELIEF MODEL TO ASSESS PREDICTORS FOR COVID-19 VACCINATION IN RILEY COUNTY, KANSAS - Liu, Yibo (My University, 2021)
In the United States, there have been approximately 45 million total COVID-19 cases, and the number is still increasing as of October 2021, despite vaccine availability. During this same period, Riley County, Kansas, has had a total of 7,994 positive cases of COVID-19 (October 14, 2021). Using the Health Belief Model (HBM), this study aimed to assess predictors of Riley County residents’ intent to get vaccinated against COVID-19 with one of the three major vaccines. The study employed a cross-sectional online survey (n=572) that was administered to Riley County residents. Results indicate that all aspects of the HBM are significantly correlated with intention to vaccinate, except cues to action. Interestingly, this study finds that participants who are between 38-47 years old perceive higher levels of COVID-19 severity than participants who are over 57. Participants who are between 18-27 also perceive lower levels of susceptibility than all other age groups. Furthermore, there is a significant positive correlative relationship between influenza vaccination and COVID-19 vaccine intention. Additionally, this study demonstrates the need for public health professionals and healthcare practitioners to foster interpersonal relationships with younger people to enhance vaccine adoption. Focus on increasing perceptions of susceptibility to and severity of vaccine-preventable diseases, on increasing perceptions of self-efficacy, and on decreasing perceptions of barriers to vaccination are important.
Keywords: health belief model; Covid-19; Vaccination